2010
DOI: 10.1089/end.2009.0318
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Stent-Related Symptoms Between Conventional Double-J Stents and a New-Generation Thermoexpandable Segmental Metallic Stent: A Validated-Questionnaire-Based Study

Abstract: The ureteral stent symptom questionnaire revealed that pain, urinary symptoms index, and general health were statistically better in the Memokath group. The Memokath group significantly outperformed the Double-J stent group in terms of the light and heavy activity. In terms of future stent insertion, patients preferred the Memokath stent. In the subgroup who had experienced both stents, the Memokath questionnaire revealed improvements in the domain of pain and the lower urinary tract symptoms index, though thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 16 publications
1
48
0
1
Order By: Relevance
“…Overall 31.8% of patients with double J stents were extremely bothered by urinary symptoms compared with 5.6% with Memokath 051 TM stents. Furthermore, 66.7% of patients with double J stents had a negative view toward living with their current urinary symptoms compared with 35.3% with Memokath 051 TM stents [33] . In addition to the above-mentioned benefits, repeated double J stent changes are avoided and pressure on hospital beds and costs (materials, hospital services, anaesthetic support, theatre, recovery etc.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall 31.8% of patients with double J stents were extremely bothered by urinary symptoms compared with 5.6% with Memokath 051 TM stents. Furthermore, 66.7% of patients with double J stents had a negative view toward living with their current urinary symptoms compared with 35.3% with Memokath 051 TM stents [33] . In addition to the above-mentioned benefits, repeated double J stent changes are avoided and pressure on hospital beds and costs (materials, hospital services, anaesthetic support, theatre, recovery etc.)…”
Section: Discussionmentioning
confidence: 99%
“…They also appear to have a lower incidence of associated lower urinary tract symptoms which are so common with double J stents, although we have not directly looked at this in our current study. Our group has previously compared QOL in patients with Memokath 051 TM stents versus double J stents [33] . In this study nearly 70% of patients with double J stents experienced urine frequency every 2 h or less compared with 47% of patients with Memokath 051 TM stents.…”
Section: Discussionmentioning
confidence: 99%
“…Countries where healthcare is more competitive, demand-led and relatively autonomous, such as Austria, Germany, France and Italy, report much shorter waiting times [16] . Waiting times can be a major issue also for our stone patients who will have to tolerate temporary measures such as a JJ stent for long periods of time and will develop interim complications that could have been avoided with immediate treatment [17] . One option to avoid this, albeit at high costs, is to send patients to private contractors or foreign countries, should state provision fail or not be in time, as reported from Portugal.…”
Section: Discussionmentioning
confidence: 99%
“…A current study by Maan et al [8] revealed that ureteral stents (Memokath 051) are more tolerable than double-J stents concerning pain, lower urinary tract symptoms, and quality of life. In the literature, the follow-up periods of Memokath stents range from 11 to 17.1 months [9,10].…”
Section: Discussionmentioning
confidence: 86%